Arti Penting Strategi Perang Toyotomi Hideyoshi dalam Mempersatukan Jepang Tahun 1554-1598 - Pandu, Rifqy Pandu (KARMAWIBANGGA: Historical Studies Journal, 2020)
This study aims: 1) to know the background of Toyotomi Hideyoshi to unite Japan, 2) to know Toyotomi Hideyoshi's war strategy to unite Japan 3) to know the political policies initiated by Toyotomi Hideyoshi The method used is the literature method. Collecting data by collecting sources in books, journals, theses and the internet. The steps in the research are as follows, heuristics, source criticism and interpretation and historiography. The research results describe that 1) Toyotomi dedicates himself to Oda Nobunaga who has a vision, and is innovative in various fields, making Toyotomi Hideyoshi a factor in becoming a leader who later replaced Oda Nobunaga as the unifier of Japan. 2) Toyotomi strategy, namely the strategy of balancing, control and command, intelligence and maturity to reap. 3) Political policies initiated by Toyotomi Hideyoshi: Forming a board of 5 administrators, 1588 enforcing a policy of confiscating weapons, holding a national census and cleaning up Rounin, measuring land ownership, improving infrastructure, reforming currencies and prohibiting slave trade.